2019
DOI: 10.1111/ejn.14618
|View full text |Cite
|
Sign up to set email alerts
|

Number of subjects required in common study designs for functional GABA magnetic resonance spectroscopy in the human brain at 3 Tesla

Abstract: Magnetic resonance spectroscopy (MRS) is a research tool for measuring the concentration of metabolites such as γ‐aminobutyric acid (GABA) and glutamate in the brain. MEGA‐PRESS has been the preferred pulse sequence for GABA measurements due to low physiological GABA concentrations, hence low signal. To compensate, researchers incorporate long acquisition durations (7–10 min) making functional measurements of this metabolite challenging. Here, the acquisition duration and sample sizes required to detect specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The inconsistent results are likely to arise from differences in stimulation intensity and electrode location, for instance. However, spurious findings with small samples also constitute a problem: some tDCS/spectroscopy studies have sample sizes around n = 10, which is plainly underpowered as recently demonstrated (Sanaei Nezhad et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results are likely to arise from differences in stimulation intensity and electrode location, for instance. However, spurious findings with small samples also constitute a problem: some tDCS/spectroscopy studies have sample sizes around n = 10, which is plainly underpowered as recently demonstrated (Sanaei Nezhad et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A higher SNR that increases linearly with the magnetic eld strength enables more accurate detection of weak signals from neurotransmitters in smaller voxels and with shorter measurement times 26 . Neurotransmitters were measured within M1 using a voxel size of 8 cm 3 (2×2×2) at 7T in this study; however, a voxel size of 27 cm 3 (3×3×3) was selected at 3T 27,28 . The 3T MRS is relatively insensitive to subtle changes in neurotransmitters underscoring cognitive functions due to large MRS voxel sizes 29 .…”
Section: Discussionmentioning
confidence: 99%
“…T2-weighted images were acquired at the rst visit (after the T1 image) and reviewed by a paediatric neuroradiologist (SS) to rule out NF1 associated tumours. The sample size of 30 participants in this study, powered on the expected change of 20% in GABA following tDCS based on our previous work (24).…”
Section: Experimental Procedures -Cross Over Intervention Designmentioning
confidence: 99%